UPAYA MENINGKATKAN JUMLAH KUNJUNGAN DESA WISATA MENGGORO MENJELANG PANDEMI COVID-19 BERAKHIR - Yulfan Arif Nurohman; Agus Setiawan; Rina Sari Qurniawati (Jurnal Pariwisata Indonesia, 2022)
Menggoro Tourism Village is one of the tourist villages that has experienced a decline in the number of domestic tourists visits due to the COVID-19 pandemic. Currently the COVID-19 pandemic has gradually subsided and government policies have begun to loosen up on the tourism sector. The community of Menggoro Village, which has experienced the economy declined for two years, needs to be improved through increasing community income. People's income can increase along with the increasing number of tourist visits This study was conducted to find the right strategy to increase the number of local tourist visits. The type of research conducted is descriptive qualitative using a SWOT analysis approach as a process of finding visits increases strategies for Menggoro Tourism Village. Based on the SWOT analysis compiled, four strategies were produced consisting of: first, the development of the Menggoro Tourism Village as halal tourism. Second, improving services and education for parties involved in tourism villages. Third, routinely carry out digital promotions. Fourth, hold cultural, local arts and religious events on a regular basis outside the traditional Jumat Pahing activities. The resulting strategy is expected to increase the number of local tourist visits which have a positive impact on the community's economy.